Oppenheimer [videorecording (DVD)] - Nolan, Christopher, 1970-; Murphy, Cillian, 1976-; Blunt, Emily; Damon, Matt; Downey, Robert, Jr., 1965-; Branagh, Kenneth; Pugh, Florence, 1996-; Safdie, Benny; Angarano, Michael; Oldman, Gary; Hartnett, Josh, 1978-; Arnold, Dylan; et al. (Universal, 2023)
The story of American scientist J. Robert Oppenheimer and his role in the development of the atomic bomb.